General election 15: usage and gratification of Sin Chew Daily's facebook news portal among UTAR undergraduates - Wong, Zhi Qing (2024)
In the era of technology, social media has become a tool among undergraduate students to get news about GE15 from Sin Chew Daily’s Facebook news portal. General Election-15 (GE-15) has brought about a significant change for Malaysia. Concurrently, social media, especially Facebook, has been essential in determining the news agenda and making it possible for all citizens to be informed about the latest information, issues, and crises. The majority of them have used social media since they were young, and their motivations for using it vary depending on what stage of life they are in. The objective of this research is to find out what the usage of Sin Chew Daily’s Facebook News Portal on GE15 among UTAR undergraduates and how the usage of Sin Chew Daily’s Facebook News Portal on GE15 gratifies UTAR undergraduate needs. A questionnaire was distributed online to 100 undergraduate students from the UTAR Sungai Long campus to implement the quantitative technique. The result of the research concludes that the higher usage of UTAR Sungai Long campus undergraduate students using Sin Chew Daily’s Facebook news portal is to liking and sharing the posts and they are gratified by the need for information and social connection.